Design guidelines for GaSb/InAs TFET exploiting strain and device size. (March 2017) - Visciarelli, Michele; Gnani, Elena; Gnudi, Antonio; Reggiani, Susanna; Baccarani, Giorgio
Abstract: A simulation study exploring the possibility of performance improvements for GaSb/InAs nanowire TFETs under appropriate stress conditions is carried out. It is demonstrated that biaxial tensile strain induces a remarkable enhancement of the on-state current thanks to bandgap reduction; however, a degradation of the ambipolar behavior is observed as well. Some stress intensity values and device geometry configurations are investigated. The best simulated device can achieve an on/off current ratio of about 3 × 10 7 with I ON ≈ 0.33  mA/ μ m at V DD = 0.3  V.